Agro-Morphological Characterization and Nutritional Profiling of Traditional Himalayan Crop Landraces for Their Promotion Toward Mainstream Agriculture - Malhotra, Nikhil; Sharma, Paras; Sood, Hemant; Chandora, Rahul; Arya, Mamta; Rana, Jai Chand; Singh, Mohar (Frontiers in Plant Science, 2022)
The northwest Indian Himalayas often regarded as biological hotspot for presence of rich agro-biodiversity harbours locally adapted traditional crop landraces facing utter neglect owing to modern agricultural systems promoting high yielding varieties. Addressing this challenge requires extricating the potential of such cultivars in terms of agro-morphological and nutritional attributes. In the present study, 29 traditional crop landraces of maize (11), paddy (07), finger millet (03), buckwheat (05) and naked barley (03) were characterized and evaluated for target traits of interest. In maize, Chitkanu emerged as an early maturing landrace (107 days) with high concentrations of zinc (Zn), iron (Fe) and potassium (K), and Safed makki showed highest 100-seed weight (28.20 g). Similarly, Bamkua dhan exhibited high concentrations of K and phosphorus (P) and Lamgudi dhan showed high protein content (14.86 g/100g) among paddy landraces. Ogla-I and Phapra-I showed high contents of protein (14.80 g/100g) and flavonoids (20.50 mg/g) among buckwheat landraces, respectively followed by Nei-I which exhibited highest protein content (15.66 g/100g) among naked barley landraces. Most of the target traits varied significantly (p < 0.05) among evaluated samples, except those associated with finger millet landraces. The grouping pattern obtained by principal component analysis (PCA) and multidimensional scaling (MDS) was congruent with geographical relationship among the crop landraces. The study led to identification of elite crop landraces having useful variations that could be exploited in plant breeding programs and biofortification strategies for future crop improvement. Our endeavour would aid in conserving the depleting Himalayan agro-biodiversity and promoting versatile traditional crops towards mainstream agriculture vis-à-vis future nutritional security.